A NOVEL PERSPECTIVE ON THE APPLICATION OF THE SHARI'AH PRINCIPLE OF MASLAHAH FOR NATIONAL INTEGRATION IN NIGERIA - Adam Yusuf Adam (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2023)
This paper examines the purpose of why Shari’ah is divinely revealed to unify human social strata. This stemmed from the basis where the Shari’ah itself is derived, that is Tawhid. Tawhid commands unification and encourages integration through understanding and constructive engagements based on mutual benefit, otherwise known as Maṣlahah. Maṣlahah is an important Shari’ah principle meant to nurse diversity and prevents discord. In governance, Maṣlahah is an important legal doctrine that accommodates ideas to help in developing public confidence to strike a balance between the statutory legislation produced by the authority and the public to adjust towards them. However, Nigeria as a country is faced with multifaceted challenges, from insurgency, banditry, and kidnapping to ethnic and religious conflicts among others. These threatened its survival as one entity and is setting it on a path to disintegration. Thus, the paper employed a historical-analytical approach in exploring the doctrine of Maṣlahah for national integration in Nigeria. It underpins that the ethnoreligious plurality of Nigeria must be seen as a means of understanding and strength, not hate and division. Similarly, the societal problems bedevilling Nigeria that including social insecurity can be managed through the Shari’ah principle of Maṣlahah, particularly Shura (consultative forum) and the re-institutionalization of an effective social justice system called al- ͨadalatul Ijtima’iyyah. Hence, the reasons given for the application of Maṣlahah as a viable means for national integration prove the idea as a novel in providing security for national building and prosperity.